2018
DOI: 10.1080/15384101.2017.1407894
|View full text |Cite
|
Sign up to set email alerts
|

Tumour-suppressive microRNA-424-5p directly targets CCNE1 as potential prognostic markers in epithelial ovarian cancer

Abstract: An accumulated evidence supports that MicroRNAs (miRNAs) have shown a prominent role in pathological processes and different tumor onset. However, to date, the potential functional roles and molecular mechanisms by how microRNA-424-5p(miR-424-5p) affects cancer cell proliferation are greatly unclear, especially in epithelial ovarian cancer(EOC).In this study, we demonstrated that miR-424-5p was significantly down-regulated in EOC tissues and cell lines. The level of miR-424-5p was negatively correlated with tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 36 publications
2
31
0
Order By: Relevance
“…There is a growing consensus that miR-424 exerts a suppressive effect on cell proliferation and cell cycle progression (Liu et al, 2018;Pande et al, 2018;Wang J. et al, 2018). Nonetheless, some studies have indicated that miR-424 could promote cell differentiation by targeting the cell cycle regulator, Cdc25A, to enhance cell cycle arrest (Sarkar et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing consensus that miR-424 exerts a suppressive effect on cell proliferation and cell cycle progression (Liu et al, 2018;Pande et al, 2018;Wang J. et al, 2018). Nonetheless, some studies have indicated that miR-424 could promote cell differentiation by targeting the cell cycle regulator, Cdc25A, to enhance cell cycle arrest (Sarkar et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has suggested that miR-424-5p functions as a tumor suppressor in breast cancer [ 40 ]. MiR-424-5p inhibits CCNE1 expression (encoding cyclin E1) in ovarian cancer, and inhibits cell cycle by suppressing the E2F transcription factor 1 (E2F1)-RB transcriptional corepressor (PRb) pathway, which promotes apoptosis [ 41 ]. Progression of malignant tumors, such as colon carcinoma, epithelial ovarian cancer, and cervical cancer involves miR-424-5p [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our ndings uncover the signi cance of the interaction between MYLK-AS1 and miR-424-5p in tumorigenesis given that MYLK-AS1 exerts oncogenic behavior partly via sponging miR-424-5p in HCC cells. In addition, miR-424-5p functions as a tumor suppressor and directly targets CCNE1 as potential prognostic markers in epithelial ovarian cancer [25] .…”
Section: Discussionmentioning
confidence: 99%